Initial development of Peltophorum dubium seedlings under physical protectors with different brightness levels - Klein, Jeferson; Rodrigues, Joao Domingos [UNESP]; Kestring, Debora; Rampim, Leandro; Aleixo, Valdemir; Battistus, Andre Gustavo (Univ Federal Mato Grosso, 2017)
The use of shelters has been shown to be an efficient technique for successful direct seeding of different species, mainly native plants. Given the importance of the species Peltophorum dubium for use in the resettlement of degraded areas, tree planting and landscaping, this study aimed to determine the physiological initial Peltophorum dubium plantlets subjected to influence of protective physical brightness with different rates. The experiment was conducted in pots filled with Haplorthox. The treatments were: no physical protector (APF); physical protector transparent (PFT); physical protector transparent + blue cellophane (PFA) and physical protector transparent red cellophane (PFV). Seedlings were evaluated at 31, 51, 71, 91, 111 and 131 days after seeding. Were evaluated the characteristics: seedling height, stem diameter, leaf area, dry leaf, stem and shoot. The results showed that both the physical protector blue as red, increased seedling height. However, lower values were obtained in biometric seedlings such treatment after the removal of guards. Reducing the brightness inversion behavior promoted seedling, having smaller diameter neck after 51 DAS. The adoption of physical protector transparent allow adequate development of seedlings with low interference in morphometric characteristics.
Keywords: canafistula; reforestation; revegetation; direct sowing; native species